Preharvest sprays with sodium nitroprusside induce resistance in harvested muskmelon against the pink rot disease. Issue 4 (22nd February 2021) - Wang, Bin; He, Xingfen; Bi, Yang; Jiang, Hong; Wang, Yi; Zheng, Xiaoyuan; Prusky, Dov
Abstract: Pink rot caused by Trichothecium roseum is an important postharvest disease of muskmelon, and caused very serious postharvest losses. In this study, sodium nitroprusside (SNP), an exogenous nitric oxide donor, was applied four times during fruit development to muskmelon. The effect of SNP sprays on pink rot in harvested fruit and the influence on the mechanism of antioxidant enzymes and the phenylpropanoid pathway were investigated. The results showed that SNP sprays significantly reduced decay incidence and lesion area of muskmelon inoculated with T. roseum . SNP sprays induced the production of H2 O2 in fruit at harvest, maintained cell membrane integrity, and increased the activity of superoxide dismutase, catalase, peroxidase, and ascorbate peroxidase during storage. In addition, SNP sprays also increased the activity of phenylalanine ammonia‐lyase, cinnamate‐4‐hydroxylase, and 4‐coumaroyl‐CoA ligase, and promoted the accumulation of total phenolic, flavonoid, and lignin content in harvested muskmelon at harvest and during storage. These results suggesting a new possible way of prevention of postharvest pathogens. Practical applications: Muskmelon is an important cash crop in the world, due to its unique appearance and intrinsic quality. However, postharvest losses of the muskmelon fruit are serious. Pink rot caused by Trichothecium roseum is one of the main reasons for the postharvest losses of harvested muskmelon. SNP preharvest sprays effectively induced the resistance and reduced decay incidence and lesion area of muskmelon inoculated with T. roseum . Compared with the postharvest treatment, which involves complete exposure, preharvest sprays not only affects the fruit, but also other portions of the plants, which could indirectly affect fruit quality. In addition, the preharvest treatment operation is simple and convenient, and the control effect is better than the postharvest treatment. Therefore, this work may provide a new approach for the control of postharvest diseases of muskmelon.